Preparação e caracterização de nanohíbridos poliméricos para aplicação em camada ativa de dispositivos optoeletrônicos - Luiza De Lazari Ferreira (2019)
In this work, hybrid of multi walled carbon nanotubes (MWCNT) and conjugated polymers (CP), two polythiophene derivatives (P3HT - poly (3-hexylthiophene) and PEDOT - poly (3,4- ethylenedioxythiophene)) and one polyaniline derivative were synthesized (PANI). Structural, optoelectronic and electrochemical characterizations were performed for all materials. The main objective of this work is to obtain charge transfer materials, processable, which high mobility nanoredes in the polymer matrix to act as traps for electrons therefore, presenting highpotential for application in optoelectronic devices. First, MWCNT functionalization were performed three stages: (i) oxidation in acidicmedium; (ii) amine addition (DAP 1,3-diaminopropane and TEPA tetraethylenepentamine); and (iii) the monomers addition (TCA - thiophenecarboxylic acid, to obtain polythiophene-derived hybrids, and ABA - aminobenzoic acid, to obtain polyaniline-derived hybrids). Later, the conductive polymers were covalently bound to these materials by polymerization in situ in oxidative medium. Electrochemical characterization (cyclic voltammetry and impedance spectroscopy)and electrical characterization of the polythiophene derived hybrids showed a superiority of the MWCNT-TC-P3HT hybrid, containing TEPA and P3HT, compared to the other materials. This material was chosen for application as an active layer of solar cell prototypes in the configuration: ITO/PEDOT: PSS/MWCNT-TC-P3HT/Al. The devices showed goodresults in the solar simulator tests and are potential candidates for application in solar cells. The hybrids derived from PANI were electrochemically characterized in two electrolytes, 2 mol L-1 HCl e 2 mol L-1 H2SO4, in order to evaluate the contribution of the nature of the electrolytes to the electrochemical properties of the materials. The analyses showed improved properties of the hybrid compared to the pure polymer in the two electrolytes. The results obtained in HCl presented systems with lower resistance in the charge transfer.